Policultivo integrado multitrófico do camarão-rosa Farfantepenaeus paulensis (Decapoda: Penaeidae) com a ostra do mangue Crassostrea brasiliana (Bivalvia: Ostreidae) em sistema de bioflocos - Lopes, Victor Hugo Polachini [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The objective of this study was to evaluate the use of Crassostrea brasiliana (mangrove oyster) as a biofilter in the integrated multitrophic polyculture with Farfantepenaeus paulensis (pink shrimp) in a biofloc system (Biofloc technology - BFT) for the production of live shrimp bait (between 4 and 5 grams). To perform the experiment, the animals were submitted to different storage densities in four treatments (T-1: 16 shrimp and 12 oysters; T-2: 16 shrimp and 24 oysters; T-3: 24 shrimp and 12 oysters; T-4: 24 shrimp and 24 oysters) in a biofloc system. The physical-chemical parameters of the water (temperature, dissolved oxygen, salinity, pH and alkalinity) as well as the nitrogen compounds (nitrite and ammonia), remained in constant monitoring and control. The animals' survival was checked every two days, and the biometrics of the schrimp were performed fortnightly. The generalized linear model (GLzM) was applied to verify the zootechnical performance of shrimp (biomass increment) and the influence of total suspended solids (TSS) between treatments over time. There was no significant difference in the Kaplan-Meier survival curve (reaffirmed by the log-rank test) for both species between treatments. Through the evaluation of the stomach contents of oysters it was observed that they consumed the bioflocs, with the majority of individuals with a full stomach, without the presence of pseudofeces. The results found through the tests performed (GLzM), registered variations over time and between treatments, both for increasing biomass of shrimp, as for total suspended solids (TSS), where it was registered that the covariates oysters and shrimp, were not able to significantly influence TSS concentrations. Regarding the zootechnical performance of the shrimp, even with a survival rate above 65%, it was observed that it can be improved, for the oysters the rate was less than 36%. The schrimp reached the average weight stipulated by the market demand for live bait in all treatments. Oysters were able to filter and feed on bioflocals, reinforcing their propensity as a biofilter organism in BFT systems. The evaluation of C. brasiliana as a biofilter in the polyculture of F. paulensis in BFT systems is unprecedented, and this study is important due to the use of native species, for the improvement of this technology.

O objetivo deste estudo foi avaliar a utilização da Crassostrea brasiliana (ostra-do-mangue) como biofiltro no policultivo integrado multitrófico com Farfantepenaeus paulensis (camarão-rosa) em sistema de bioflocos (Biofloc technology - BFT) para a produção de isca viva de camarão (entre 4 e 5 gramas). Para execução do experimento os animais foram submetidos a diferentes densidades de estocagem em quatro tratamentos (T-1: 16 camarões e 12 ostras; T-2: 16 camarões e 24 ostras; T-3: 24 camarões e 12 ostras; T-4: 24 camarões e 24 ostras) em sistema de bioflocos. Os parâmetros físico-químicos da água (temperatura, oxigênio dissolvido, salinidade, pH e alcalinidade) assim como os compostos nitrogenados (nitrito e amônia), mantiveram-se em constante monitoramento e controle. A sobrevivência dos animais foi verificada a cada dois dias, e as biometrias dos camarões realizadas quinzenalmente. O modelo linear generalizado (GLzM) foi aplicado para verificar o desempenho zootécnico dos camarões (incremento biomassa) e a influência dos sólidos suspensos totais (SST) entre os tratamentos ao longo do tempo. Não houve diferença significativa na curva de sobrevivência de Kaplan-Meier (reafirmadas pelo teste de log-rank) para ambas espécies entre os tratamentos. Através da avaliação do conteúdo estomacal das ostras observou-se que estas consumiram o bioflocos, com a maioria dos indivíduos com o estômago cheio, sem a presença de pseudofezes. Os resultados encontrados através dos testes realizados (GLzM), registraram variações ao decorrer do tempo e entre os tratamentos, tanto para incremento de biomassa dos camarões, quanto para de sólidos suspensos totais (SST), onde registrou-se que as covariáveis ostras e camarões, não foram capazes de influenciar de maneira significativa sobre as concentrações de SST. A respeito do desempenho zootécnico dos camarões mesmo com uma taxa de sobrevivência acima de 65% observou-se que pode ser melhorado, já para as ostras a taxa foi menor que 36%. Os camarões atingiram o peso médio estipulado pela demanda de mercado de isca viva em todos os tratamentos. As ostras foram capazes de filtrar e se alimentar do bioflocos, reforçando sua propensão como organismo biofiltrador em sistemas de BFT. A avaliação da C. brasiliana como biofiltro no policultivo de F. paulensis em sistemas de BFT é algo inédito, sendo importante este estudo devido ao uso das espécies nativas, para o aprimoramento desta tecnologia.
Multitrophic integrated polyculture of the pink shrimp Farfantepenaeus paulensis (Decapoda: Penaeidae) with the mangrove oyster Crassostrea brasiliana (Bivalvia: Ostreidae) in a biofloc system
Keywords: Bioflocos; Carcinicultura; Espécies nativas; Ostreicultura; Policultivo integrado multitrófico